The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1600-9657.2008.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

A 6‐year investigation into types of dental trauma treated in a paediatric dentistry clinic in Eastern Anatolia Region, Turkey

Abstract: The purpose of this study was to assess the frequency, the effective factors and the applied treatments for dental trauma among children aged 1-15 years from Eastern Anatolia in a 6-year period. The total frequency of trauma in this study was calculated as 4.9% during a 6-year period. The males were found to have more traumatic injury than females (P < 0.05). Also, the permanent teeth were more vulnerable to dental trauma than the primary teeth (P < 0.05). The highest frequency of traumas in the primary teeth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
78
3
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(127 citation statements)
references
References 18 publications
25
78
3
15
Order By: Relevance
“…A lack of motor coordination 25,26 on walking and running is the main reason for TDI in preschool children, whereas in early school-age children, TDIs are most likely due to increased independence at school, playgrounds and sports 4,27,28 . In agreement with previous studies [18][19][20]29,30 , this study showed that TDI commonly involved maxillary incisors. Th is fi nding may be explained by the fact that these teeth may have inadequate lip coverage and frequently protrude 30 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A lack of motor coordination 25,26 on walking and running is the main reason for TDI in preschool children, whereas in early school-age children, TDIs are most likely due to increased independence at school, playgrounds and sports 4,27,28 . In agreement with previous studies [18][19][20]29,30 , this study showed that TDI commonly involved maxillary incisors. Th is fi nding may be explained by the fact that these teeth may have inadequate lip coverage and frequently protrude 30 .…”
Section: Discussionsupporting
confidence: 93%
“…Th e most common type of trauma in primary teeth was subluxation. Periodontal tissue injuries in primary dentition occurred 2.8 times more often than hard dental tissue injuries, a result similar to other studies 3,16,20,28,32 . Th is fi nding can be explained by the periodontal ligament elasticity and alveolar bone resilience 26,30 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations